Analysis of Arrhenius Activation Energy and Chemical Reaction in Nanofluid Flow and Heat Transfer Over a Thin Moving Needle - Hussain, I. S.; Prakash, D.; Abdalla, Bahaaeldin; Muthtamilselvan, M. (Current Nanoscience, 2023)
Objective: A numerical and theoretical study is developed to analyze the combined effect of activation energy and chemical reaction in the flow of nanofluids due to the thin moving needle using the mathematical nanofluid model offered by Buongiorno. A passively controlled nanoparticle volume fraction boundary is assumed rather than actively controlled. Methods: A similarity transformation is utilized to convert the governing partial differential equations to a set of ordinary differential equations which are then solved numerically by Runge-Kutta Shooting Method (RKSM). The physical characteristics of flow, heat and mass transfer are illustrated via graphs and tables for some set of values of governing parameters. Results: In addition, the basic non-linear governing equations are solved analytically using semianalytical technique called Differential transform method (DTM) and the comparison has been made with the numerical and the published results. Conclusion: The present study reveals that the ratio between the needle velocity and the composite velocity brings out to increases the velocity distribution with λ<0. Moreover, the activation energy influences the chemical species to react from the thickness of the concentration layer η=0.6 and the fraction of nanoparticles to the fluid is significantly more away from the needle surface.
Keywords: thermophoresis